Interstitial cystitis—an imbalance of risk and protective factors? - Westropp, Jodi L.; Stella, Judith L.; Buffington, C. A. Tony (Frontiers in Pain Research, 2024)
Interstitial cystitis (IC) presents as a chronic pain condition with variable combinations of symptoms depending on the species and individual patient. It is diagnosed by the presence of lower urinary tract signs and symptoms in combination with a variety of comorbid health problems, a history of life adversities, and the absence of other conditions that could cause the lower urinary tract signs. IC occurs naturally in humans and cats as a dimensional condition, with patients presenting with mild, moderate, and severe symptoms. Most patients appear to recover without specific treatment. A number of rodent models of IC have been used to study its causes and treatments. Unfortunately, current therapies generally fail to ameliorate IC symptoms long-term. The recent classification of IC as a chronic primary pain disorder calls for a rethinking of current clinical and research approaches to it. Beginning when a patient encounters a clinician, precipitating, perpetuating, and palliating risk factors can be addressed until a cause or reliably effective therapy is identified, and identifying predisposing and preventive factors can inform epidemiological studies and health promotion interventions. Predisposing, precipitating, and perpetuating risk factors, including environmental, psychological, and biological, increase the activity of the central threat response system (CTRS), which plays a clinically important role in IC symptoms. Studies in cats and rodent models have revealed that environmental enrichment (EE), in the absence of bladder-directed therapies, leads to amelioration of IC symptoms, implying a central role for the CTRS in symptom precipitation and perpetuation. Conceptually moving the source of IC pain to the brain as a motivational state rather than one resulting from peripheral nociceptive input offers both clinicians and researchers novel opportunities to improve care for patients with IC and for researchers to use more ecologically valid rodent models. It may even be that IC results from an excess of risk to protective factors, making this imbalance a targetable cause rather than a consequence of IC.